VD_FINDINFO HC / 2019 / 200 vom 18. März 2019 - VD Tribunal cantonal (2019)
PERTE DE SOUTIEN, LÉGITIMATION ACTIVE ET PASSIVE, EXPERTISE, FAUTE, ACCIDENT DE LA CIRCULATION | 45 al. 3 CO, 31 LCR, 36 LCR, 55 CPC (CH)